1994
DOI: 10.1007/bf01698487
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand disease as a cause of recurrent mucocutaneous bleeding in primary thrombocythemia: Relationship with platelet count

Abstract: SummaryWe present a 4-year follow-up of a 42-yearold patient with primary thrombocythemia whose clinical course was complicated by two major mucocutaneous bleeding episodes. On both occasions an acquired functional yon Willebrand factor deficiency was demonstrated. In contrast to what is reported in the literature, an inverse relationship between platelet number and plasma high-molecular-weight multimers of von Willebrand factor was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 15 publications
4
66
0
Order By: Relevance
“…In a previous study we showed that plasma vWF:CBA/ vWF:Ag ratios are tightly correlated to the percentage of plasma large vWF multimers [16]. The ristocetin cofactor activity, which is usually used to test vWF function in vitro, appeared to be a less sensitive parameter for detecting modest reductions of large vWF multimers in plasma, consistent with previous observations [7,14,16]. The influence of a decreased level of large vWF multimers in plasma on the excessive ASA-induced BT prolongation was stressed by manipulating the plasma levels of large vWF multimers by the infusion of DDAVP.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In a previous study we showed that plasma vWF:CBA/ vWF:Ag ratios are tightly correlated to the percentage of plasma large vWF multimers [16]. The ristocetin cofactor activity, which is usually used to test vWF function in vitro, appeared to be a less sensitive parameter for detecting modest reductions of large vWF multimers in plasma, consistent with previous observations [7,14,16]. The influence of a decreased level of large vWF multimers in plasma on the excessive ASA-induced BT prolongation was stressed by manipulating the plasma levels of large vWF multimers by the infusion of DDAVP.…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies we found that the reduction of large vWF multimers in plasma in ET is directly related to the number of circulating platelets [4,14,17]. The reduction of large vWF multimers in plasma becomes particularly apparent at platelet counts exceeding 1000!…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…While extreme thrombocytosis may correlate with the occurrence of hemorrhage due to an acquired von Willebrand disease, [19][20][21] the contribution of platelet number to major thrombotic events remains poorly established. 22 In a randomized clinical trial that included high-risk ET patients, HU treatment was found to be superior to anagrelide, a selective cytoreductive antiplatelet drug, in preventing arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%